Electrical matrix stimulation suppresses acute itch independently of activation of sleeping nociceptors - Schwarzenauer, Miriam; Rukwied, Roman; Lampert, Angelika; Rolke, Roman; Namer, Barbara (European journal of pain, 2023)
Introduction Itch can be reduced by pain. Activation of sleeping nociceptors (CMi) is a crucial mechanism for the peripheral component of intense and long-lasting pain. Thus, activation of CMi might be especially effective in itch reduction. Electrical stimulation using sinusoidal pulses activates CMi with tolerable pain intensity, whereas short rectangular pulses with low intensity do not. In humans, histaminergic itch is mediated by histamine-sensitive CMi, whereas other pruritogens activate polymodal nociceptors (CM). Methods In a psychophysical approach in a balanced crossover repeated-measures design in healthy volunteers, we activated nociceptors by two different electrical stimulation paradigms via a matrix electrode: 4 Hz sinusoidal pulses that activate C-nociceptors including CMi or 4 Hz rectangular stimuli to activate nociceptors excluding CMi. After 5-min stimulation, itch was induced by either histamine iontophoresis or application of cowhage spicules. Itch ratings were assessed via a numerical rating scale (NRS). Results Electrical 4 Hz sine wave stimulation (0.1 mA) with low pain ratings of 1.5 (NRS; 0-10) induced an axon reflex erythema (3 cm2), indicating activation of CMi, whereas rectangular 0.2 ms pulses (average 0.91 mA) with the same pain rating did not. Both electrical stimulation paradigms reduced itch magnitude over time evoked by either histamine or cowhage to a similar extent. Peak maximum itch evoked by histamine was reduced by both stimulation paradigms, but not cowhage maximum itch. Discussion Since electrical stimulation with the rectangular pulse paradigm reduces itch to a similar extent as the sine wave stimulation paradigm, the input of CMi is not necessarily required for itch suppression. The input of A-fibres and polymodal nociceptors, similarly, as also achieved by scratching, seems to be sufficient for both forms of chemically evoked itch. Significance Since activation of CMi does not provide additional benefit for itch suppression, spinal pain pathways transmitted via CM versus CMi have differential effects on itch-processing circuits. This is important knowledge for using electrical matrix stimulation as itch suppressor since activation of sleeping nociceptors either requires significantly painful stimulation paradigms or specialized stimulation paradigms as sinusoidal pulses. An alternative approach using half-sine wave pulses with low pain intensity activating specifically polymodal nociceptors to suppress itch via matrix electrode stimulation may be considered.
Gesehen am 23.10.2023